Characterization of influenza H1N1 Gag virus-like particles and extracellular vesicles co-produced in HEK-293SF. Issue 47 (8th November 2019) - Venereo-Sánchez, Alina; Fulton, Kelly; Koczka, Krisztina; Twine, Susan; Chahal, Parminder; Ansorge, Sven; Gilbert, Rénald; Henry, Olivier; Kamen, Amine
Highlights: Extracellular vesicles (EVs) are co-produced with influenza virus-like particles (VLPs) in HEK293 cells. RNA, DNA, total proteins are quantified in VLP production samples and EV control samples. nanoLC-MS/MS analyses allow characterization of protein content of VLPs and EVs. Specific proteins were uniquely identified in different preparations of VLPs and EVs. Abstract: One of the concerns associated with the use of influenza virus-like particles (VLPs) as vaccine candidate or delivery system is their heterogeneous composition. Enveloped VLPs take up the host cell membrane at the budding site carrying out not only the viral antigenic proteins but also host proteins. In addition, the intrinsic nature of cells to produce membrane derived vesicles or extracellular vesicles (EVs), which have similar size to the VLPs, makes VLP purification process challenging. To further characterize these particles and identify proteins that are unique to each population, comparative proteomic analyses were completed to ultimately provide guidance for rational design of separation protocols. The VLPs were produced in suspension and serum free media by transient transfection of an inducible clone of a Human Embryonic Kidney (HEK-293SF) cells expressing HA and NA (H1N1/A/Puerto Rico/8/34), with a plasmid containing the gag gene of HIV-1 fused to GFP. EVs were produced independently from the non-transformed HEK-293SF cell line as a control for comparative studies. Both preparations were characterized for total nucleic acids and protein concentrations and extensively analyzed by nanoLC-MS/MS for their protein compositions. The proteomic analyses showed that aside from the recombinant VLP proteins, nucleolin was the most abundant host cell protein uniquely identified within VLPs (considering the MASCOT score value) while lactotransferrin and heat shock protein 90 were the most abundant proteins in EVs. Overall, this comparative study identifies potential target proteins as specific markers to guide VLP purification and discusses the biogenesis of enveloped particles released in HEK-293 cell suspension cultures emphasizing on the biological functions of host cell proteins identified.